(untitled) (Journal of Nuclear Technology in Applied Science, 2018)
Removal of malachite green dye (MG) from industrial wastewater has been investigated using low density polyethylene (LDPE)-grafted–gly cidylmethacrylate (GMA) then chemically modified with diethylamine (DEA), hydroxylamine (HA) or phosphoric acid (H3PO4). The effects of various factors; initial dye concentration, pH, contact time, temperature …etc on the adsorption process were studied and optimal experimental conditions were ascertained. The adsorption of MG on the prepared ad sorbents were confirmed by Fourier Transform Infrared (FTIR) and Scan ning Electron Microscopy (SEM). The contact time at equilibrium was found to be 120 minutes at pH=5.8 and temperature 40oC. Langmuir and Freundlich isotherms were applied to the data obtained at equilibrium. The maximum removal of dye was found to be 98% for the grafted film treated with phosphoric acid indicating that the prepared films would be a good alternative for the removal of MG dye from wastewater with high efficiency and good tool economically.